Broken glass, broken world : glass in French culture in the aftermath of 1870 - Scott, Hannah (Research monographs in French studies, 2016)
Crystal palaces and railway stations, greenhouses and arcades, church windows and shop frontages, wine glasses and lamp shades: from the monumental to the minuscule, glass became increasingly pervasive in nineteenth-century France. Yet as the bombshells and fires of the Année Terrible wreaked havoc upon Paris in 1870-71, this modern dreamland was harrowed by the sight and sound of shattering glass. In this interdisciplinary study, Hannah Scott combines cultural history with close literary analyses of fictional works by three major authors from the period: Emile Zola's Au Bonheur des Dames (1883), Guy de Maupassant's Contes et nouvelles (1870-1891), and Joris-Karl Huysmans's decadent masterpiece, À rebours (1884). She explores the distressing freight of meaning attached to glass for readers in the wake of the Année Terrible, before Symbolism and the Art Nouveau could purify the material world of its haunting past.